2022
DOI: 10.3390/jpm12071160
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sonophoresis with Corticosteroids in Carpal Tunnel Syndrome: Systematic Review and Meta-Analysis

Abstract: Carpal tunnel syndrome is a neuropathic disease. It is one of the most frequent musculoskeletal pathologies affecting the upper limbs. One of most frequently used non-surgical treatments is corticosteorids. There are several alternatives for corticosteroids administration. One of them is phonophoresis, this being an effective and painless method of treatment. A systematic review and meta-analysis have been conducted over the use of phonophoresis with corticosteroids for the treatment of carpal tunnel syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 56 publications
6
3
0
Order By: Relevance
“…When iontophoresis was compared to local injection of corticosteroids in the study by Aygül et al [27], the control intervention showed better results for median sensory nerve conduction velocity. Dexamethasone and betamethasone were the main drugs used in our included trials, which agrees with the previous review of Martín-Vega et al [11] that examined the effects of phonophoresis in the same target population. The use of these drugs has been reported to be effective for pain and inflammatory processes [34,35].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…When iontophoresis was compared to local injection of corticosteroids in the study by Aygül et al [27], the control intervention showed better results for median sensory nerve conduction velocity. Dexamethasone and betamethasone were the main drugs used in our included trials, which agrees with the previous review of Martín-Vega et al [11] that examined the effects of phonophoresis in the same target population. The use of these drugs has been reported to be effective for pain and inflammatory processes [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…However, no therapeutic supremacy was recorded in the meta-analysis against comparator interventions [21][22][23][24][25]27]. This is in line with the results reported by Martín-Vega et al [11], in which the…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations